Gender lens review of adolescent health care services: a mixed methods study in Bangladesh - Fariha Haseen; Hridi Hedayet; Shahana Nazneen; Nurjahan Akter; Umme Haney; Md Sunyet Alam Chowdhury; Md Saidur Rahman Khan; AGM Mashuqur Rahman; Nazma Siddika Begum; Mohd Shahdt Hossain Mahmud; Syed Shariful Islam (Journal of Global Health Reports)
# Background